Improving Teacher Performance in Implementing Effective Learning Through Class Observation Supervision at MIN 8 West Aceh - Nurdin Nurdin (ISTIFHAM, 2023)
The purpose of this school action research is to determine the increase in teacher performance in carrying out effective learning through classroom observation supervision at MIN 8 West Aceh and to find out the effectiveness of classroom observation supervision in improving teacher performance in carrying out effective learning at MIN 8 West Aceh. The subjects in this study were all teachers at MIN 8 West Aceh, totaling 54 people. Data collection techniques used are observation and questionnaires. This research was carried out in two cycles: planning, implementation, observation, and reflection. The data analysis technique used is the descriptive percentage. The results of the study show that the supervision of the principal is very influential in improving teacher performance on learning effectiveness. This is evidenced by an increase in teacher performance in each cycle, namely, the percentage of teacher completeness in cycle I reached 53.7%, while in cycle II, it reached 81.5%. Of the 54 teachers at MIN 8 West Aceh, after the action was carried out in cycle II, almost all had the awareness to improve their performance. This will have an impact on improving the quality of education in schools. Based on the results of the research above, the results of increasing teacher performance in carrying out effective learning reached 81.5%, so the supervision of class observations was said to be effective.